The effect of omega-3 PUFA Liposan-3 on the content of essential fatty acids in lipid serum of rats with avitaminosis F - V. M. Batig (Journal of Education, Health and Sport, 2019)
Background. Determine the effect of the drug "Liposan-3" on the content of PUFA in the serum lipids of rats receiving a fat-free diet. Methods. Used the drug "Liposan-3α" containing 14% PUFA with a ratio of ω-6/ω-3 of 0.49. Rats were fed a semi-synthetic fat-free diet for 21 days (group 1), supplemented with 0.5 % liposan (group 2) or 1.0 % liposan (group 3). Controlled changes in live weight and feed intake. After euthanasia, the content of triglycerides, total cholesterol was determined in the blood serum, and the content of PUFA was determined in the fractions of neutral lipids (triglycerides + cholesterol esters) and free fatty acids. In addition, the content of malondialdehyde (MDA), the activity of catalase, and the antioxidant-prooxidant API index were determined in their blood serum. Results. The actual liposan intake was 86.8 mg/kg per day, in terms of the amount of PUFA 11.9 mg/kg, including 8.1 mg/kg ω-3 PUFA. The animal weight gain increased by 30 %, the content of TG and cholesterol remained within the normal range, there was no increase in the content of MDA, the activity of catalase did not decrease, and the API index increased. The content of ω-6 PUFA decreased in both fractions of serum lipids by 19-22 %, however, the containment of ω-3 PUFA increased by 2.5-3 times, while the ratio of ω-6/ω-3 PUFA decreased by 2.3- 3.3 times. Conclusion. The drug "Liposan-3" in doses of 80-130 mg/kg increases the content in blood serum lipids of ω-3 PUFA and normalizes the ratio of ω-6/ω-3 of PUFA. Liposan-3 does not increase lipid peroxidation and has a stimulating effect on the growth of animals.